2014
DOI: 10.1016/j.neuron.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Integration of Task-Relevant Visual Features in Posterior Parietal Cortex

Abstract: Summary The primate visual system consists of multiple hierarchically organized cortical areas, each specialized for processing distinct aspects of the visual scene. For example, color and form are encoded in ventral pathway areas such as V4 and inferior temporal cortex, while motion is preferentially processed in dorsal pathway areas such as the middle temporal area. Such representations often need to be integrated perceptually to solve tasks which depend on multiple features. We tested the hypothesis that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 55 publications
10
75
0
1
Order By: Relevance
“…This is consistent with previous reports of LIP direction tuning during both passive viewing and complex tasks 33,34 , and likely reflects LIP’s interconnection with upstream motion processing areas such as MT, the medial superior temporal (MST) 35 , and the ventral intraparietal 3638 . Interestingly a recent study using a variant of a motion direction DMS task found delay-period direction encoding in MST but not MT 39 .…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous reports of LIP direction tuning during both passive viewing and complex tasks 33,34 , and likely reflects LIP’s interconnection with upstream motion processing areas such as MT, the medial superior temporal (MST) 35 , and the ventral intraparietal 3638 . Interestingly a recent study using a variant of a motion direction DMS task found delay-period direction encoding in MST but not MT 39 .…”
Section: Discussionsupporting
confidence: 92%
“…FBA affects LIP neurons in a spatially global manner as feature tuning shifts toward the relevant features, consistent with our earlier report (Ibos and Freedman, 2014), were qualitatively independent of the spatial position of attention. However, SBA modulated FBA effects as the amplitudes of feature-tuning shifts were larger when behaviorally-relevant stimuli were located inside neurons’ RFs.…”
Section: Introductionsupporting
confidence: 91%
“…SBA or FBA have both been shown to enhance encoding of task relevant locations or features throughout the visual cortical hierarchy (Cohen and Maunsell, 2011; Connor et al, 1997; Ipata et al, 2012; Martinez-Trujillo and Treue, 2004; Maunsell and Treue, 2006) as well as higher order areas such as the Lateral Intraparietal (LIP) area (Bisley and Goldberg, 2010; Herrington and Assad, 2009; Ibos and Freedman, 2014), frontal-eye field (FEF) (Armstrong et al, 2009; Ibos et al, 2013; Zhou and Desimone, 2011) and prefrontal cortex (PFC) (Bichot et al, 2015; Hussar and Pasternak, 2013; Lennert and Martinez-Trujillo, 2011, 2013; Tremblay et al, 2015). Moreover, the impact of SBA and FBA on the response of visual cortical neurons suggests that both types of attention modulate neuronal processing in similar ways (Cohen and Maunsell, 2009, 2011; Hayden and Gallant, 2009; Leonard et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations